Economic assimilation of Mexicans and Central Americans in the United States - Giovanni Peri; Zachariah Rutledge (IZA Journal of Development and Migration, 2022)
Using United States Census data between 1970 and 2017, we analyze the economic assimilation of subsequent arrival cohorts of Mexicans and Central Americans by comparing their earnings and employment probability to those of natives with similar age and education. We find that, on average, these immigrants started with an earnings gap of 40-45% and eliminated half of it within 20 years of arrival. Recent cohorts that arrived after 1995 performed better than earlier cohorts in that they had smaller initial earnings gaps and faster convergence. Additionally, the most recent cohorts entered the United States without an employment rate disadvantage, and they surpassed natives within 10 years. We also find that Mexicans and Central Americans working in the construction sector and those living in nonenclave and urban areas had faster earnings convergence than the others.
Keywords: J15; J24; J61; 330; economic assimilation; earnings; employment; Mexicans and Central Americans; cohort analysis